Implementation of a metastatic malignancy of unknown primary origin service led by a palliative physician. Issue 1 (1st January 2018) - Brooks, David; Hughes, Philippa; Farrington, Clare; Bath, Peter A; McGregor, Mary; Ahmed, Wasim; Noble, Bill
ABSTRACT: Background : Cancer of unknown primary is the fourth most common cause of cancer death in the United Kingdom. National guidance in 2010 recommended the establishment of a dedicated unknown primary team to facilitate targeted investigation and symptom control. A service development project was undertaken to identify those affected by malignancy of unknown origin and institute a pathway for coordinating their care led by a palliative physician. Method: In order to describe the patient population and illness trajectory and to assess the effect of the new pathway on the clinical outcomes we used a retrospective and prospective comparative case notes survey to identify the pre- and post-pathway population. This took place in secondary care. Inclusion criteria were patients with metastatic disease with no known primary; exclusion criteria were where the site of metastasis was so suggestive of a primary that it would be managed as per that disease process. 88 patients were included.Results : Mean age was 72.5 years. The mean survival time from presentation was 81.8 days. There was no difference pre or during pathway implementation in age, performance status or survival time. There was no reduction in the numbers referred for tumour directed therapy. There was a non-statistically significant reduction in the number who died in hospital during the pathway implementation. Conclusions : This study suggests having a metastatic malignancy of unknown primary origin service led by a palliative physician does not reduce the number referred for tumour directed therapy. It also adds evidence of the poor prognosis and thus the need for early palliative care input.